1995
DOI: 10.1254/jjp.67.395
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ethanol and Crocin on the Induction of Long-Term Potentiation in the CA1 Region of Rat Hippocampal Slices

Abstract: ABSTRACT-The effects of ethanol and crocin on the induction of long-term potentiation (LTP) were investigated in the CAI region of rat hippocampal slices in vitro. Ethanol (50-75 mM) suppressed the LTP induced by strong tetanic stimulation (51 pulses at 100 Hz). Crocin (20 rM) did not affect the baseline synaptic responses, but significantly prevented the LTP-suppressing action of ethanol. This effect of crocin was concentration dependent (10 -30 pM). Crocin (20 pM) alone did not affect the potentiation induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
4

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 15 publications
2
26
0
4
Order By: Relevance
“…Additionally, we showed that LTP was attenuated following the application of both moderate (20 mM) and high (50 mM) levels of EtOH. Accordingly, the gradual decrease in the magnitude of LTP as the result of an increase in EtOH concentration has been reported by several groups in the CA1 (Izumi et al, 2007;Lovinger et al, 1990;Sugiura et al, 1995).…”
Section: Attenuation Of Ltp In Control Animals Following Acute Etoh Asupporting
confidence: 56%
“…Additionally, we showed that LTP was attenuated following the application of both moderate (20 mM) and high (50 mM) levels of EtOH. Accordingly, the gradual decrease in the magnitude of LTP as the result of an increase in EtOH concentration has been reported by several groups in the CA1 (Izumi et al, 2007;Lovinger et al, 1990;Sugiura et al, 1995).…”
Section: Attenuation Of Ltp In Control Animals Following Acute Etoh Asupporting
confidence: 56%
“…The concentration of ethanol required for LTP inhibition, however, has varied widely among reports. While many studies have found that ethanol inhibits LTP induction at concentrations of 50 mM or more (Randall et al, 1995;Sugiura et al, 1995;Schummers et al, 1997), some reports have shown that concentrations as low as 5 mM also impair LTP induction (Blitzer et al, 1990). The inconsistencies in these studies may reflect experimental differences including slice Correspondence: Yukitoshi Izumi, M.D., Ph.D., Department of Psychiatry, Washington University School of Medicine, 660 South Euclid, Box 8134, St. Louis, MO 63110, USA, Phone: +1 314 362 8659, Fax: +1 314 747 2983, Email: izumiy@psychiatry.wustl.edu Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is termed long‐term potentiation (LTP), and is widely believed to be part of the cellular basis of learning and memory. As a plausible explanation for ethanol‐induced memory impairments, several groups have reported that ethanol inhibits the induction of LTP in hippocampal slices in vitro ( Sinclair & Lo, 1986 ; Blitzer et al ., 1990 ; Morrisett & Swartzwelder, 1993 ; Sugiura et al ., 1995 ). However, two questions remained to be solved.…”
Section: Introductionmentioning
confidence: 99%